RADIODIAGNOSIS AND CLINICAL SIGNIFICANCE OF THE CALCIUM MILK PHENOMENON IN UROLOGY - V. M. Buylov; T. V. Bubnova; Yu. N. Patrunov; Yu. B. Smolyakov; I. A. Makeev (Вестник рентгенологии и радиологии)
Objective – to determine the clinical significance and capabilities of radiodiagnosis of the calcium milk phenomenon in urology. Material and methods. In 1989–2014, a total of 59 patients with calyceal diverticula (CDs) were followed up with ultrasound, plain intravenous urography (IVU), and 64-slice spiral computed tomography (MSCT). Results. Nine (15%) patients were found to have a calcium milk phenomenon as echo-positive by ultrasonography and as X-ray contrast-positive by IVU and MSCT of the CD cavity contents shifting during polypositional examination. Instead of repeated CT scanning, delayed IVU was performed to reduce radiation exposure. Conclusion. Polypositional examination revealing the shifting horizontal level of calcium milk must be necessary performed in the radiodiagnosis of the calcium milk phenomenon. The clinical significance of the calcium milk phenomenon, like multiple small stones detected in CD, is the lack of indications for telelithotripsy. Calcium milk in the renal cysts is of no clinical significance.